Preparation method of quartz crucible and quartz crucible

By forming a dense protective coating on the inner surface of the quartz crucible, the problem of poor bonding force of the transparent layer of the quartz crucible and the protective coating in the prior art is solved, the corrosion resistance and service life are improved, and the production efficiency of single crystal silicon is improved. and cost.

CN119161197APending Publication Date: 2024-12-20JINKO SOLAR CO LTD

Patent Information

Application Number
CN202411297908.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the production process of single crystal silicon, the transparent layer of the existing quartz crucible is easily corroded by molten silicon, resulting in a short service life and an increase in production cost. The bonding force between the protective coating and the inner surface of the crucible is poor and it is easy to fall off.

Method used

The crucible embryos of the first quartz sand layer and the second quartz sand layer are sequentially arranged from the outside to the inside, and the transparent layer and bubble layer are formed by arc firing, and the inner surface is sprayed with barium hydroxide, nanosilicon dioxide and The protective coating of boric acid, combined with carbon dioxide gradient heating heat treatment, forms a dense and uniform protective coating, including barium carbonate, nanosilicon dioxide and barium borate.

Benefits of technology

It improves the corrosion resistance and service life of the quartz crucible, enhances the bonding force between the protective coating and the inner surface of the crucible, and improves the crystal formation rate and crystal rod quality of single crystal silicon.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161197A_ABST
    Figure CN119161197A_ABST
Patent Text Reader

Abstract

The preparation method of the quartz crucible comprises the following steps that a crucible green body is prepared, the crucible green body comprises a first quartz sand layer and a second quartz sand layer which are sequentially arranged from outside to inside, and the second quartz sand layer comprises quartz sand and barium carbonate; the purity of the quartz sand in the first quartz sand layer is smaller than that of the quartz sand in the second quartz sand layer; the crucible green body is fired, and a crucible body is obtained; a protective coating is sprayed to the inner surface of a crucible body through inert gas, then gradient heating heat treatment is conducted after carbon dioxide gas is introduced, the quartz crucible is obtained, the quartz crucible comprises the crucible body and a protective layer located on the inner surface of the crucible body, and the protective layer comprises barium carbonate, nano silicon dioxide and barium borate. According to the preparation method of the quartz crucible, the binding force between the protective coating and the inner surface of the quartz crucible can be improved, the corrosion resistance of the quartz crucible is improved, and the service life of the quartz crucible is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of crucible production, and in particular to a preparation method of a quartz crucible and the quartz crucible. Background Art

[0002] In the production process of single crystal silicon, the quartz crucible is a key equipment for carrying molten silicon. Its corrosion resistance and thermal stability directly affect the production efficiency and cost of single crystal silicon. At present, the quartz crucible used in the production process of single crystal silicon is usually translucent, with an inner and outer layer structure. The outer layer is a high bubble density area, called the bubble composite layer. The bubble composite layer has a high bubble content and can evenly radiate the radiation heat source provided by the heater, thereby ensuring that the quartz crucible in the heat field can evenly radiate the radiation heat source provided by the heater; the inner layer is a transparent layer, called the bubble depletion layer. The existence of the bubble depletion layer can reduce the bubble density in the contact area between the crucible and the solution, thereby improving the success rate of single crystal growth and the quality of the crystal rod.

[0003] In the production process of single crystal silicon, molten silicon reacts with the quartz crucible at high temperatures, causing severe corrosion of the transparent layer of the quartz crucible, thereby affecting the crystallization rate and quality of the single crystal silicon. Therefore, in order to reduce the corrosion of the transparent layer of the quartz crucible by molten silicon, it is usually necessary to add a layer of protective coating to the inner surface of the quartz crucible. However, the existing coating has poor bonding with the inner surface of the crucible and is easy to fall off in a high temperature environment, resulting in a shorter service life of the quartz crucible and increased production costs. Summary of the invention

[0004] The present application provides a method for preparing a quartz crucible and a quartz crucible, which can form a dense and uniform protective coating on the inner surface of the quartz crucible, and make the protective coating have excellent adhesion to the inner surface of the quartz crucible, thereby improving the corrosion resistance and service life of the quartz crucible.

[0005] In a first aspect, the present application provides a method for preparing a quartz crucible, comprising the following steps:

[0006] preparing a crucible green body, wherein the crucible green body comprises a first quartz sand layer and a second quartz sand layer arranged in sequence from outside to inside, wherein the second quartz sand layer comprises quartz sand and barium carbonate, and the purity of the quartz sand in the first quartz sand layer is lower than the purity of the quartz sand in the second quartz sand layer;

[0007] Firing the crucible green body to obtain a crucible body;

[0008] The protective coating is sprayed onto the inner surface of the crucible body by using an inert gas, and then a gradient temperature increase heat treatment is performed after carbon dioxide gas is introduced to obtain a quartz crucible, wherein the protective coating includes 35wt% to 45wt% of barium hydroxide, 2.8wt% to 5wt% of nano-silicon dioxide and 4wt% to 10wt% of boric acid in mass percentage, and the quartz crucible includes a crucible body and a protective layer located on the inner surface of the crucible body, and the protective layer includes barium carbonate, nano-silicon dioxide and barium borate.

[0009] In some embodiments, the amount of quartz sand added to the first quartz sand layer is 95 g to 100 g.

[0010] In some embodiments, the amount of quartz sand added to the second quartz sand layer is 10 g to 15 g.

[0011] In some embodiments, the mass ratio of the quartz sand to the barium carbonate in the second quartz sand layer is (10-15): (0.003-0.005).

[0012] In some embodiments, the purity of the quartz sand in the first quartz sand layer is 6N-13N.

[0013] In some embodiments, the purity of the quartz sand in the second quartz sand layer is greater than 7N.

[0014] In some embodiments, the crucible green body is arc fired to obtain a crucible body, wherein the arc firing temperature is 1700° C. to 2600° C. and the time is 30 min to 40 min.

[0015] In some embodiments, the step of spraying the protective coating onto the inner surface of the crucible body using an inert gas comprises:

[0016] Under vacuum conditions, the protective coating is sprayed onto the inner surface of the crucible body at a distance of 25 cm to 30 cm from the inner surface of the crucible body using a spray gun with a pressure of 20 psi to 40 psi.

[0017] In some embodiments, the vacuum degree under the vacuum condition is 1200Pa to 15000Pa.

[0018] In some embodiments, the spraying thickness of the protective coating is controlled to be in the range of 0.01 mm to 0.015 mm; and / or the spraying temperature of the protective coating is controlled to be in the range of 25° C. to 35° C.

[0019] In some embodiments, the gradient temperature increase heat treatment includes: after introducing carbon dioxide gas, heating to 40°C~45°C at 5°C / min~10°C / min for heat treatment for 5min~10min, and then heating to 75°C~80°C at 5°C / min~10°C / min for heat treatment for 15min~20min.

[0020] In some embodiments, the flow rate of the carbon dioxide gas is 40 L / min to 100 L / min, and the introduction time is 25 min to 30 min.

[0021] In a second aspect, the present application provides a quartz crucible, which is prepared according to the preparation method of the quartz crucible described in the first aspect, and the quartz crucible includes a protective layer, a transparent layer and a bubble layer arranged in sequence from the inside to the outside, wherein the protective layer includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer includes quartz sand and barium silicate.

[0022] In some embodiments, the protective layer has a thickness of 0.01 mm to 0.015 mm.

[0023] In some embodiments, the mass percentage of barium silicate in the transparent layer is 0.05 ppm to 0.1 ppm.

[0024] In some embodiments, the transparent layer has a thickness of 5 mm to 10 mm.

[0025] In some embodiments, the bubble layer has a thickness of 12 mm to 15 mm.

[0026] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:

[0027] The preparation method of the quartz crucible provided in the present application comprises the following steps: firstly, preparing a crucible embryo, wherein the crucible embryo comprises a first quartz sand layer and a second quartz sand layer sequentially arranged from the outside to the inside, wherein the second quartz sand layer comprises quartz sand and barium carbonate, and the purity of the quartz sand in the first quartz sand layer is lower than the purity of the quartz sand in the second quartz sand layer, so that the transparent layer of the quartz crucible can reduce the bubble density in the contact area with the solution, thereby improving the crystallization rate and crystal rod quality of single crystal silicon; then, the crucible embryo is fired, so that the quartz sand in the first quartz sand layer and the second quartz sand layer are melted to form a crucible body, and at the same time, the barium carbonate is evenly distributed on the inner surface of the crucible body and decomposed into barium oxide during the firing process, which reacts with the silicon dioxide component in the quartz sand on the inner surface of the crucible body to form a barium silicate coating, which can improve the heat resistance and chemical stability of the quartz crucible, improve the first rod crystallization rate and crystal rod quality of single crystal silicon, and also improve the adhesion between the protective coating and the quartz crucible; then, using the inert The gas sprays the protective coating containing barium hydroxide, nano-silicon dioxide and boric acid onto the inner surface of the crucible body. During the spraying process, the inert gas can reduce unnecessary reactions between the protective coating and moisture or oxygen in the air, thereby improving the quality and stability of the protective coating. Finally, carbon dioxide gas is introduced for gradient heat treatment. During the heat treatment process, barium hydroxide reacts with carbon dioxide gas to generate barium carbonate, which is adsorbed and deposited on the surface of the barium silicate coating. Boric acid, as a flux, can reduce the melting point of the protective coating and promote the protective coating to form a dense protective coating. At the same time, boric acid reacts with barium hydroxide to generate barium borate, which can improve the thermal expansion coefficient of nano-silicon dioxide, thereby reducing the gap between the thermal expansion coefficient of the protective coating and the thermal expansion coefficient of nano-silicon dioxide, and improving the thermal stability and adhesion of the protective coating. In addition, nano-silicon dioxide can fill the pores in the protective coating, thereby improving the density and mechanical strength of the protective coating. The preparation method of the above-mentioned quartz crucible first forms a uniformly distributed barium silicate coating on the inner surface of the quartz crucible, and then forms a dense and uniform protective coating on the surface of the barium silicate coating through a spraying process combined with heat treatment. The bonding force between the protective coating and the inner surface of the quartz crucible can be improved, and the thermal stability and chemical stability of the coating can be improved, thereby improving the corrosion resistance and service life of the quartz crucible. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0029] Figure 1 A process flow chart of the preparation of a quartz crucible provided in an embodiment of the present application;

[0030] Figure 2 A schematic diagram of the structure of a quartz crucible provided in an embodiment of the present application.

[0031] Figure 2 middle:

[0032] 1. Protective coating; 2. Transparent layer; 3. Bubble layer. DETAILED DESCRIPTION

[0033] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0034] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0036] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0037] In the production process of single crystal silicon, the quartz crucible is a key equipment for carrying molten silicon. Its corrosion resistance and thermal stability directly affect the production efficiency and cost of single crystal silicon. At present, the quartz crucible used in the production process of single crystal silicon is usually translucent, with an inner and outer layer structure. The outer layer is a high bubble density area, called the bubble composite layer. The bubble composite layer has a high bubble content and can evenly radiate the radiation heat source provided by the heater, thereby ensuring that the quartz crucible in the heat field can evenly radiate the radiation heat source provided by the heater; the inner layer is a transparent layer, called the bubble depletion layer. The existence of the bubble depletion layer can reduce the bubble density in the contact area between the crucible and the solution, thereby improving the success rate of single crystal growth and the quality of the crystal rod.

[0038] In the production process of single crystal silicon, molten silicon reacts with the quartz crucible at high temperatures, causing severe corrosion of the transparent layer of the quartz crucible, thereby affecting the crystallization rate and quality of the single crystal silicon. Therefore, in order to reduce the corrosion of the transparent layer of the quartz crucible by molten silicon, it is usually necessary to add a layer of protective coating to the inner surface of the quartz crucible. However, the coating has poor bonding with the inner surface of the crucible and is easy to fall off in a high temperature environment, resulting in a shorter service life of the quartz crucible and increased production costs.

[0039] In a first aspect, the present application provides a method for preparing a quartz crucible. Figure 1The process flow chart of the preparation process of the quartz crucible provided in the embodiment of the present application is as follows: Figure 1 As shown, the following steps are included:

[0040] Step S100, preparing a crucible green body, the crucible green body comprising a first quartz sand layer and a second quartz sand layer arranged in sequence from the outside to the inside, wherein the second quartz sand layer comprises quartz sand and barium carbonate, and the purity of the quartz sand in the first quartz sand layer is lower than the purity of the quartz sand in the second quartz sand layer;

[0041] Step S200, firing the crucible green body to obtain the crucible body;

[0042] Step S300, using an inert gas to spray a protective coating onto the inner surface of a crucible body, and then introducing carbon dioxide gas to perform a gradient temperature increase heat treatment to obtain a quartz crucible, wherein the protective coating includes 35wt% to 45wt% of barium hydroxide, 2.8wt% to 5wt% of nano-silicon dioxide and 4wt% to 10wt% of boric acid by weight percentage, and the quartz crucible includes a crucible body and a protective layer located on the inner surface of the crucible body, and the protective layer includes barium carbonate, nano-silicon dioxide and barium borate.

[0043] The preparation method of the quartz crucible provided in the present application comprises the following steps: firstly, preparing a crucible embryo, wherein the crucible embryo comprises a first quartz sand layer and a second quartz sand layer sequentially arranged from the outside to the inside, wherein the second quartz sand layer comprises quartz sand and barium carbonate, and the purity of the quartz sand in the first quartz sand layer is lower than the purity of the quartz sand in the second quartz sand layer, so that the transparent layer of the quartz crucible can reduce the bubble density in the contact area with the solution, thereby improving the crystallization rate and crystal rod quality of single crystal silicon; then, the crucible embryo is fired, so that the quartz sand in the first quartz sand layer and the second quartz sand layer are melted to form a crucible body, and at the same time, the barium carbonate is evenly distributed on the inner surface of the crucible body and decomposed into barium oxide during the firing process, which reacts with the silicon dioxide component in the quartz sand on the inner surface of the crucible body to form a barium silicate coating, which can improve the heat resistance and chemical stability of the quartz crucible, improve the first rod crystallization rate and crystal rod quality of single crystal silicon, and also improve the adhesion between the protective coating and the quartz crucible; then, using the inert The gas sprays the protective coating containing barium hydroxide, nano-silicon dioxide and boric acid onto the inner surface of the crucible body. During the spraying process, the inert gas can reduce unnecessary reactions between the protective coating and moisture or oxygen in the air, thereby improving the quality and stability of the protective coating. Finally, carbon dioxide gas is introduced for gradient heat treatment. During the heat treatment process, barium hydroxide reacts with carbon dioxide gas to generate barium carbonate, which is adsorbed and deposited on the surface of the barium silicate coating. Boric acid, as a flux, can reduce the melting point of the protective coating and promote the protective coating to form a dense protective coating. At the same time, boric acid reacts with barium hydroxide to generate barium borate, which can improve the thermal expansion coefficient of nano-silicon dioxide, thereby reducing the gap between the thermal expansion coefficient of the protective coating and the thermal expansion coefficient of nano-silicon dioxide, and improving the thermal stability and adhesion of the protective coating. In addition, nano-silicon dioxide can fill the pores in the protective coating, thereby improving the density and mechanical strength of the protective coating. The preparation method of the above-mentioned quartz crucible first forms a uniformly distributed barium silicate coating on the inner surface of the quartz crucible, and then forms a dense and uniform protective coating on the surface of the barium silicate coating through a spraying process combined with heat treatment. The bonding force between the protective coating and the inner surface of the quartz crucible can be improved, and the thermal stability and chemical stability of the coating can be improved, thereby improving the corrosion resistance and service life of the quartz crucible.

[0044] The following is an introduction to the preparation method of the quartz crucible of the present application in combination with the specific process:

[0045] Step S100, preparing a crucible green body, the crucible green body comprising a first quartz sand layer and a second quartz sand layer arranged in sequence from outside to inside, wherein the second quartz sand layer comprises quartz sand and barium carbonate, and the purity of the quartz sand in the first quartz sand layer is lower than the purity of the quartz sand in the second quartz sand layer.

[0046] In the above scheme, by controlling the purity of the quartz sand in the first quartz sand layer to be lower than the purity of the quartz sand in the second quartz sand layer, the bubble density in the contact area of ​​the transparent layer of the quartz crucible with the solution can be reduced, thereby improving the single crystal formation rate and the quality of the crystal rod.

[0047] In some embodiments, the step of preparing a crucible green body includes: placing quartz sand into a rotating crucible mold, and the quartz sand forms a first quartz sand layer on the inner wall of the crucible mold under the action of centrifugal force, and then placing a mixture of quartz sand and barium carbonate into the crucible mold, and forming a second quartz sand layer on the surface of the first quartz sand layer under the action of centrifugal force to obtain a crucible green body.

[0048] In some embodiments, the purity of the quartz sand in the second quartz sand layer is greater than 7N, that is, the purity is greater than 99.99999%, which can improve the purity of the transparent layer of the quartz crucible and reduce impurities in the transparent layer of the quartz crucible, thereby improving the crystallization rate of silicon and the quality of the crystal rod in the single crystal silicon preparation process.

[0049] In some embodiments, the amount of quartz sand added to the first quartz sand layer is 95g to 100g, specifically 95g, 96g, 97g, 98g, 99g or 100g, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0050] In some embodiments, the amount of quartz sand added to the second quartz sand layer is 10 g to 15 g, specifically 10 g, 11 g, 12 g, 13 g, 14 g or 15 g, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0051] In some embodiments, the mass ratio of quartz sand to barium carbonate in the second quartz sand layer is (10-15)-(0.003-0.005), specifically 10:0.003, 10:0.004, 10:0.005, 12:0.004, 13:0.003, 14:0.005, 15:0.003 or 15:0.005, etc. Of course, it can also be other values ​​within the above range, which is not limited here. It can be understood that by controlling the mass ratio of quartz sand to barium carbonate in the second quartz sand layer within the above range, the barium carbonate can be evenly distributed on the inner surface of the crucible body and react with the silicon dioxide on the inner surface of the crucible body to form a barium silicate coating, which can improve the thermal stability and chemical stability of the quartz crucible and promote the rapid formation of a quartz crystal layer on the inner surface of the quartz crucible during the preparation of single crystal silicon, thereby improving the crystallization rate and crystal rod quality of single crystal silicon. At the same time, it can ensure that the barium ion content in the silicon solution is low, thereby increasing the minority carrier lifetime of the crystal rod.

[0052] In some embodiments, the purity of the quartz sand in the first quartz sand layer is 6N-13N, specifically 6N, 7N, 8N, 9N, 10N, 11N, 12N or 13N, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0053] Step S200, firing the crucible green body to obtain the crucible body.

[0054] In some embodiments, the crucible green body is arc fired to obtain the crucible body. The specific process of arc firing is: current is passed above the crucible mold containing the crucible green body to form an arc at a high temperature of 1700°C to 2600°C, slowly melting the quartz sand in the first quartz sand layer and the second quartz sand layer in the crucible green body to form a crucible body with an inner and outer two-layer structure.

[0055] In the present application, the first quartz sand layer and the second quartz sand layer in the crucible embryo can be melted by arc firing to form a crucible body with an inner and outer two-layer structure. Under the action of the high-temperature arc, the first quartz sand layer is melted to form an outer layer structure of the crucible body. The outer layer structure is a region with a high bubble density, called a bubble layer. The bubble layer has a high bubble content and can evenly radiate the radiation heat source provided by the heater, thereby ensuring that the quartz crucible in the hot field can evenly radiate the radiation heat source provided by the heater. The second quartz sand layer is melted to form an inner layer structure. The inner layer structure is a transparent layer. Its existence can reduce the bubble density in the contact area between the crucible and the solution, thereby improving the success rate of single crystal growth and the quality of the crystal rod. At the same time, the barium carbonate in the second quartz sand layer is evenly distributed. The barium silicate coating is distributed on the inner surface of the transparent layer and decomposes into barium oxide during the arc melting process, and then reacts with silicon dioxide in the transparent layer to form a barium silicate coating. The presence of this coating can improve the thermal stability and chemical stability of the quartz crucible, thereby improving the first rod crystallization rate and the first rod quality of single crystal silicon during the preparation of single crystal silicon; and the presence of the barium silicate coating can make the inner surface of the crucible body more uniform, which is conducive to the uniform distribution of the subsequent protective coating. At the same time, in the preparation process of the subsequent protective coating, the presence of the barium silicate coating can also provide an ideal place for the barium hydroxide in the protective coating to undergo a chemical reaction, thereby improving the bonding force between the protective coating and the inner surface of the quartz crucible, reducing the shedding of the protective coating during the preparation of single crystal silicon, thereby improving the corrosion resistance and service life of the quartz crucible.

[0056] In some embodiments, the crucible green body is arc fired to obtain the crucible body, wherein the arc firing temperature is 1700° C. to 2600° C. and the time is 30 min to 40 min.

[0057] In some embodiments, the arc burning temperature is 1700°C to 2600°C, specifically 1700°C, 1800°C, 1900°C, 2000°C, 2100°C, 2200°C, 2300°C, 2400°C, 2500°C or 2600°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0058] In some embodiments, the arc burning time is 30 min to 40 min, specifically 30 min, 32 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0059] In the present application, the temperature and time of arc melting are within the above range, so that the quartz sand in the first quartz sand layer and the second quartz sand layer can be melted to form a crucible body, and at the same time, the barium carbonate can react with the silicon dioxide in the quartz sand to form a barium silicate coating, which provides an ideal place for the chemical reaction of barium hydroxide in the subsequent protective coating preparation process, and is beneficial to improving the bonding strength between the protective coating and the inner surface of the quartz crucible.

[0060] Step S300, using an inert gas to spray a protective coating onto the inner surface of a crucible body, and then introducing carbon dioxide gas to perform a gradient temperature increase heat treatment to obtain a quartz crucible, wherein the protective coating includes 35wt% to 45wt% of barium hydroxide, 2.8wt% to 5wt% of nano-silicon dioxide and 4wt% to 10wt% of boric acid by weight percentage, and the quartz crucible includes a crucible body and a protective layer located on the inner surface of the crucible body, and the protective layer includes barium carbonate, nano-silicon dioxide and barium borate.

[0061] In the above scheme, the inert gas can reduce unnecessary reactions between the protective coating and moisture or oxygen in the air during the spraying process, thereby improving the quality and stability of the protective coating; during the heat treatment process, barium hydroxide reacts with carbon dioxide gas to generate barium carbonate, which is adsorbed and deposited on the inner surface of the crucible body. The presence of a barium silicate coating on the inner surface of the crucible body can improve the bonding strength between the protective coating and the inner surface of the crucible body; boric acid, as a flux, can lower the melting point of the protective coating and promote the protective coating to form a dense protective coating; at the same time, boric acid reacts with barium hydroxide to generate barium borate, which can improve the thermal expansion coefficient of nano-silicon dioxide, thereby reducing the gap between the thermal expansion coefficient of the protective coating and the thermal expansion coefficient of nano-silicon dioxide, thereby improving the thermal stability and adhesion of the protective coating; and nano-silicon dioxide can fill the pores in the protective coating, thereby improving the density and mechanical strength of the protective coating, thereby improving the corrosion resistance and service life of the quartz crucible.

[0062] In some embodiments, the protective coating includes 35 wt% to 45 wt% barium hydroxide by weight, specifically 35 wt%, 36 wt%, 38 wt%, 40 wt%, 41 wt%, 42 wt%, 43 wt%, 44 wt% or 45 wt%, etc., and of course other values ​​within the above range may also be possible, which are not limited here.

[0063] In some embodiments, the protective coating includes 2.8wt% to 5wt% nano-silicon dioxide by weight, specifically 2.8wt%, 2.9wt%, 3wt%, 3.5wt%, 3.8wt%, 4wt%, 4.5wt%, 4.6wt% or 5wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0064] In some embodiments, the protective coating includes 4 wt% to 10 wt% boric acid, specifically 4 wt%, 4.5 wt%, 5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 8 wt%, 9 wt% or 10 wt%, etc., and of course other values ​​within the above range are also possible, which are not limited here.

[0065] In the present application, the mass percentage of each component in the protective coating is controlled within the above range, which is beneficial to improve the bonding strength between the protective coating and the inner surface of the crucible body, reduce the shedding of the protective coating during high-temperature use, and thus improve the corrosion resistance and service life of the quartz crucible.

[0066] In some embodiments, the step of spraying the protective coating onto the inner surface of the crucible body using an inert gas includes:

[0067] Under vacuum conditions, the protective coating is sprayed onto the inner surface of the crucible body at a distance of 25 cm to 30 cm from the inner surface of the crucible body using a spray gun with a pressure of 20 psi to 40 psi. It can be understood that spraying under vacuum conditions can effectively reduce dust, oxygen and other gases in the air that may cause defects in the protective coating, reduce impurities in the protective coating, and improve the uniformity and quality of the protective coating.

[0068] In some embodiments, the inert gas includes at least one of argon, helium, krypton, and neon.

[0069] In some embodiments, the pressure of the spray gun is controlled to be 20psi to 40psi, specifically 20psi, 25psi, 28psi, 30psi, 32psi, 35psi, 38psi or 40psi, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0070] In some embodiments, the distance between the spray gun and the inner surface of the crucible body is 25 cm to 30 cm, specifically 25 cm, 26 cm, 27 cm, 28 cm, 29 cm or 30 cm, etc., and certainly other values ​​within the above range are also possible, which are not limited here.

[0071] In some embodiments, the vacuum degree under vacuum conditions is 1200Pa~15000Pa, specifically 1200Pa, 1500Pa, 2000Pa, 5000Pa, 8000Pa, 10000Pa, 12000Pa or 15000Pa, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0072] In some embodiments, the spraying temperature of the protective coating is controlled in the range of 25°C to 35°C, specifically 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 32°C or 35°C, but is not limited to the listed values, and other values ​​not listed in the above range are also applicable.

[0073] The present application controls the vacuum degree, spray gun pressure, distance from the spray gun to the inner surface of the crucible body, spray temperature and other process parameters during the spraying process, so that the protective coating can be evenly and densely coated on the inner surface of the crucible body, thereby improving the uniformity and density of the protective coating.

[0074] In some embodiments, the spraying thickness of the protective coating is controlled to be in the range of 0.01 mm to 0.015 mm, specifically 0.01 mm, 0.011 mm, 0.012 mm, 0.013 mm, 0.014 mm or 0.015 mm, etc. Of course, it can also be other values ​​within the above range, which are not limited here. It can be understood that by controlling the spraying thickness of the protective coating within the above range, the thickness of the protective coating formed on the inner surface of the quartz crucible can be controlled.

[0075] In some embodiments, the gradient temperature increase heat treatment includes: after introducing carbon dioxide gas, heating to 40°C to 45°C at 5°C / min to 10°C / min for 5min to 10min, and then heating to 75°C to 80°C at 5°C / min to 10°C / min for 15min to 20min. It can be understood that the gradient temperature increase heat treatment includes low-temperature heat treatment and high-temperature heat treatment. The present application can improve the crystallinity and adhesion of the protective coating through gradient heat treatment, thereby reducing the shedding of the protective coating during use and increasing the service life of the quartz crucible.

[0076] In the present application, the low temperature heat treatment is beneficial to promote the evaporation of water in the protective coating and the initial reaction of each component in the protective coating, thereby facilitating the subsequent reaction of the protective coating and improving the uniformity and stability of the protective coating. At the same time, the temperature of the low temperature heat treatment is relatively low, and the boric acid in the protective coating is a flux, and its effect is more obvious at a lower temperature, which can ensure that the coating can quickly form a dense structure after spraying.

[0077] Specifically, the heating rate of the low-temperature heat treatment can be 5°C / min, 5.5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc., which is not limited here. The temperature of the low-temperature heat treatment can be 40°C, 41°C, 42°C, 43°C, 44°C or 45°C, etc., which is not limited here. The time of the low-temperature heat treatment can be 5min, 5.5min, 6min, 7min, 8min, 9min or 10min, etc., which is not limited here. Preferably, the temperature of the low-temperature heat treatment is 45°C and the time is 5min.

[0078] In the present application, the high temperature section heat treatment can promote the decomposition and reaction of barium hydroxide. During the high temperature section heat treatment process, the barium hydroxide decomposes and reacts with carbon dioxide gas to form barium carbonate. At the same time, the high temperature section heat treatment can promote the dispersion and filling of nano-silicon dioxide, so that the silicon dioxide can be evenly filled in the gaps of the protective coating, thereby improving the density of the protective coating and the bonding force with the inner surface of the quartz crucible. It should be noted that the barium carbonate generated in this process can decompose at high temperature during the preparation of single crystal silicon and further react with the silicon dioxide on the inner surface of the quartz crucible to form barium silicate, thereby reducing the corrosion of the quartz crucible by molten silicon and increasing the service life of the quartz crucible.

[0079] The heating rate of the high temperature section heat treatment can be 5°C / min, 5.5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc., which is not limited here. The temperature of the high temperature section heat treatment can be 75°C, 75.5°C, 76°C, 76.5°C, 77°C, 78°C, 79°C or 80°C, which is not limited here. The time of the high temperature section heat treatment can be 15min, 16min, 16.5min, 17min, 18min, 19min or 20min, etc., which is not limited here. Preferably, the temperature of the low temperature section heat treatment is 80°C and the time is 15min.

[0080] In some embodiments, the flow rate of carbon dioxide gas is 40L / min to 100L / min, specifically 40L / min, 50L / min, 60L / min, 70L / min, 80L / min, 90L / min or 100L / min, etc., and of course, other values ​​within the above range are also possible, which are not limited here. It can be understood that the flow rate of carbon dioxide gas within the above range is conducive to controlling the reaction rate of carbon dioxide gas and barium carbonate and the generation of reaction products, which can ensure the uniformity and stability of the protective coating and improve the quality of the protective coating.

[0081] In some embodiments, the introduction time of carbon dioxide gas is 25 min to 30 min, specifically 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0082] In a second aspect, the present application provides a quartz crucible, which is prepared according to the method for preparing a quartz crucible according to the first aspect. Figure 2 A schematic diagram of the structure of a quartz crucible provided in an embodiment of the present application is shown in FIG. Figure 2 As shown, the quartz crucible includes a protective layer 1, a transparent layer 2 and a bubble layer 3 which are arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate.

[0083] In the above scheme, during the preparation of the quartz crucible, the quartz sand in the second quartz sand layer of the crucible embryo melts during the firing process to form a transparent layer 2, and at the same time, the barium carbonate in the second quartz sand layer reacts with the silicon dioxide in the quartz sand during the high-temperature melting process to be converted into barium silicate and evenly distributed in the transparent layer 2. The barium silicate in the transparent layer 2 can promote the rapid formation of cristobalite crystals on the inner surface of the quartz crucible during the preparation of single crystal silicon, thereby improving the first rod crystallization rate and the first rod quality of single crystal silicon. At the same time, the presence of barium silicate can also improve the bonding force between the protective coating 1 and the inner surface of the quartz crucible; during the preparation of the quartz crucible, the barium hydroxide in the protective coating reacts with the carbon dioxide gas during the gradient temperature increase heat treatment process to form the barium carbonate in the protective coating 1, and the barium carbonate in the protective coating 1 during the preparation of single crystal silicon It can be decomposed into barium oxide and react with silicon dioxide on the inner surface of the quartz crucible to generate barium silicate, which enhances the chemical bonding between the protective coating 1 and the quartz crucible, thereby further improving the bonding force between the protective coating 1 and the quartz crucible, and the generated barium silicate can reduce the corrosion of the quartz crucible by molten silicon; nano silicon dioxide can be filled and distributed in the pores of the protective coating 1 to improve the density and adhesion of the protective coating 1. At the same time, the presence of barium borate can not only further improve the density of the protective coating, but also improve the thermal expansion coefficient of nano silicon dioxide, thereby reducing the gap between the thermal expansion coefficient of the protective coating and the thermal expansion coefficient of nano silicon dioxide, and improving the thermal stability and adhesion of the protective coating 1, thereby reducing the shedding of the protective coating 1 during use and improving the corrosion resistance and service life of the quartz crucible.

[0084] In some embodiments, the thickness of the protective layer 1 is 0.01 mm to 0.015 mm, specifically 0.01 mm, 0.011 mm, 0.012 mm, 0.013 mm, 0.014 mm or 0.015 mm, etc. Of course, it can also be other values ​​within the above range, which are not limited here. If the thickness of the protective coating 1 is too thin, it is difficult to achieve the protective effect on the quartz crucible, and the quartz crucible is easily corroded by the silicon solution; if the thickness of the protective coating 1 is too thick, the protective coating 1 is easy to crack or fall off from the inner surface of the quartz crucible, thereby affecting the crystallization rate and crystal rod quality of the single crystal silicon.

[0085] In some embodiments, the mass percentage of barium silicate in the transparent layer 2 is 0.05ppm to 0.1ppm, specifically 0.05ppm, 0.06ppm, 0.07ppm, 0.075ppm, 0.08ppm, 0.085ppm, 0.09ppm or 0.1ppm, etc., but is not limited to the listed values, and other values ​​within the above range are also applicable. It can be understood that the mass percentage of barium silicate in the transparent layer 2 is within the above range, which can ensure that barium silicate can promote the rapid formation of cristobalite crystals on the inner surface of the quartz crucible during the preparation of single crystal silicon, thereby reducing the reaction of single crystal silicon with the quartz crucible during the high-temperature pulling process, improving the crystallization rate and crystal rod quality of single crystal silicon, and at the same time reducing the corrosion of molten silicon to the quartz crucible, and improving the strength of the quartz crucible; it can also reduce the barium ion content in the silicon solution, thereby increasing the minority carrier life of the crystal rod.

[0086] In some embodiments, the thickness of the transparent layer 2 is 5 mm to 10 mm, specifically 5 mm, 6 mm, 6.5 mm, 7 mm, 8 mm, 9 mm or 10 mm, etc., and of course, it can also be other values ​​within the above range, which is not limited here. The thickness of the transparent layer 2 within the above range is conducive to reducing the bubble density in the contact area between the quartz crucible and the solution, thereby improving the crystallization rate and crystal rod quality of the single crystal silicon.

[0087] In some embodiments, the thickness of the bubble layer 3 is 12 mm to 15 mm, specifically 12 mm, 12.5 mm, 13 mm, 13.6 mm, 14 mm, 14.8 mm or 15 mm, etc., but is not limited to the listed values, and other values ​​within the above range are also applicable. It can be understood that the bubble layer 3 is a regional layer with a high bubble density, and its function is to uniformly radiate the radiant heat source provided by the heater, thereby ensuring that the quartz crucible in the thermal field can uniformly radiate the radiant heat source provided by the heater. Controlling the thickness of the bubble layer 3 within the above range can ensure that the radiant heat source of the heater is uniform, which is conducive to providing uniform heat to the polycrystalline silicon raw material in the quartz crucible, so that the polycrystalline silicon raw material melts evenly, and improves the crystallization rate and quality of single crystal silicon during direct pulling of single crystals.

[0088] Example 1

[0089] (1) 100 kg of quartz sand with a purity of 7N is placed in a rotating crucible mold, and a first quartz sand layer is formed on the inner wall of the crucible mold under the action of centrifugal force, and then 3 g of barium carbonate powder and 10 kg of quartz sand with a purity of 8N are mixed evenly and added to the above crucible mold, and a second quartz sand layer is formed under the action of centrifugal force to obtain a crucible green body;

[0090] (2) arc firing the crucible green body to obtain a crucible body, wherein the arc firing temperature is 2000° C. and the time is 30 min;

[0091] (3) 35 wt % of barium hydroxide, 2.8 wt % of nano-silicon dioxide and 4 wt % of boric acid were uniformly mixed to obtain a protective coating;

[0092] (4) Under a vacuum degree of 2000 Pa, the protective coating was sprayed onto the inner surface of the crucible body at a distance of 25 cm to 30 cm from the inner surface of the crucible body using a spray gun with an argon pressure of 30 psi, and the spraying temperature of the protective coating was controlled to be 30° C. and the spraying thickness was 0.01 mm; then, carbon dioxide gas was introduced into the crucible body at a flow rate of 60 L / min, wherein the carbon dioxide gas was introduced for 25 min, and then the temperature was increased to 45° C. at a rate of 5° C. / min for heat treatment for 5 min, and then the temperature was increased to 80° C. at a rate of 5° C. / min for heat treatment for 15 min, to obtain a quartz crucible.

[0093] The quartz crucible prepared in this embodiment is as follows: Figure 2 As shown, the quartz crucible includes a protective layer 1 (thickness 0.01 mm), a transparent layer 2 (thickness 6 mm) and a bubble layer 3 (thickness 10 mm) arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.1 ppm.

[0094] Example 2

[0095] The difference from Example 1 is that (1) 95 kg of quartz sand with a purity of 7N is placed in a rotating crucible mold, and a first quartz sand layer is formed on the inner wall of the crucible mold under the action of centrifugal force, and then 5 g of barium carbonate powder and 15 kg of quartz sand with a purity of 8N are mixed evenly and added to the above crucible mold, and a second quartz sand layer is formed under the action of centrifugal force to obtain a crucible green body.

[0096] The quartz crucible prepared in this embodiment is as follows: Figure 2 As shown, the quartz crucible includes a protective layer 1 (thickness 0.01 mm), a transparent layer 2 (thickness 8 mm) and a bubble layer 3 (thickness 8 mm) which are arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.05 ppm.

[0097] Example 3

[0098] The difference from Example 1 is that (3) 40 wt% of barium hydroxide, 4 wt% of nano-silicon dioxide and 8 wt% of boric acid are mixed evenly to obtain a protective coating.

[0099] The quartz crucible prepared in this embodiment is as follows: Figure 2 As shown, the quartz crucible includes a protective layer 1 (thickness 0.011 mm), a transparent layer 2 (thickness 6 mm) and a bubble layer 3 (thickness 10 mm) arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.06 ppm.

[0100] Example 4

[0101] The difference from Example 1 is that (3) 45 wt% of barium hydroxide, 5 wt% of nano-silicon dioxide and 10 wt% of boric acid are mixed evenly to obtain a protective coating.

[0102] The quartz crucible prepared in this embodiment is as follows: Figure 2 As shown, the quartz crucible includes a protective layer 1 (thickness 0.012 mm), a transparent layer 2 (thickness 6 mm) and a bubble layer 3 (thickness 10 mm) arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.07 ppm.

[0103] Example 5

[0104] Different from Example 1, in step (4), the spraying thickness of the protective coating is controlled to be 0.015 mm.

[0105] The quartz crucible prepared in this embodiment is as follows: Figure 2 As shown, the quartz crucible includes a protective layer 1 (thickness 0.015 mm), a transparent layer 2 (thickness 6 mm) and a bubble layer 3 (thickness 10 mm) arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.08 ppm.

[0106] Example 6

[0107] The difference from Example 1 is that (4) under a vacuum degree of 2000 Pa, the protective coating is sprayed onto the inner surface of the crucible body at a distance of 25 cm to 30 cm from the inner surface of the crucible body using a spray gun with an argon pressure of 30 psi, and the spraying temperature of the protective coating is controlled to be 30° C. and the spraying thickness is 0.01 mm; then, carbon dioxide gas is introduced into the crucible body at a flow rate of 60 L / min, and then the temperature is increased to 40° C. at 5° C. / min for heat treatment for 10 min, and then the temperature is increased to 75° C. at 5° C. / min for heat treatment for 20 min, to obtain a quartz crucible.

[0108] The quartz crucible prepared in this embodiment is as follows: Figure 2 As shown, the quartz crucible includes a protective layer 1 (thickness 0.01 mm), a transparent layer 2 (thickness 6 mm) and a bubble layer 3 (thickness 10 mm) arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.05 ppm.

[0109] Example 7

[0110] The difference from Example 1 is that the flow rate of carbon dioxide gas in step (4) is 40 L / min.

[0111] The quartz crucible prepared in this embodiment is as follows: Figure 2 As shown, the quartz crucible includes a protective layer 1 (thickness 0.01 mm), a transparent layer 2 (thickness 6 mm) and a bubble layer 3 (thickness 10 mm) arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.05 ppm.

[0112] Example 8

[0113] The difference from Example 1 is that the flow rate of carbon dioxide gas in step (4) is 95 L / min.

[0114] The quartz crucible prepared in this embodiment is as follows: Figure 2 As shown, the quartz crucible includes a protective layer 1 (thickness 0.01 mm), a transparent layer 2 (thickness 6 mm) and a bubble layer 3 (thickness 10 mm) arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.05 ppm.

[0115] Comparative Example 1

[0116] Different from Example 1, no barium hydroxide is added to the protective coating in step (3).

[0117] The quartz crucible prepared in this comparative example, Figure 2 As shown, the quartz crucible includes a protective layer 1 (0.01 mm thick), a transparent layer 2 (6 mm thick) and a bubble layer 3 (10 mm thick) which are arranged in sequence from the inside to the outside, wherein the protective layer 1 includes nano-silicon dioxide and boric acid, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.05 ppm.

[0118] Comparative Example 2

[0119] Different from Example 1, no nano-silicon dioxide is added to the protective coating in step (3).

[0120] The quartz crucible prepared in this comparative example, Figure 2 As shown, the quartz crucible includes a protective layer 1 (0.01 mm thick), a transparent layer 2 (6 mm thick) and a bubble layer 3 (10 mm thick) which are arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.1 ppm.

[0121] Comparative Example 3

[0122] Different from Example 1, no boric acid is added to the protective coating in step (3).

[0123] The quartz crucible prepared in this comparative example, Figure 2 As shown, the quartz crucible includes a protective layer 1 (0.01 mm thick), a transparent layer 2 (6 mm thick) and a bubble layer 3 (10 mm thick) which are arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate and nano-silicon dioxide, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.1 ppm.

[0124] Comparative Example 4

[0125] Different from Example 1, (4) under the condition of vacuum degree of 12000Pa, the protective coating is sprayed on the inner surface of the crucible body at a distance of 25cm to 30cm from the inner surface of the crucible body using a spray gun with an argon pressure of 40psi, and the spraying temperature of the protective coating is controlled to be 35°C and the spraying thickness is 0.015mm.

[0126] The quartz crucible prepared in this embodiment is as follows: Figure 2 As shown, the quartz crucible includes a protective layer 1 (thickness of 0.015 mm), a transparent layer 2 (thickness of 6 mm) and a bubble layer 3 (thickness of 10 mm) which are arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium hydroxide, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.1 ppm.

[0127] Comparative Example 5

[0128] The difference from Example 1 is that (1) 100 kg of quartz sand with a purity of 7N is placed in a rotating crucible mold, and a first quartz sand layer is formed on the inner wall of the crucible mold under the action of centrifugal force, and then 10 kg of quartz sand with a purity of 8N is added to the above crucible mold, and a second quartz sand layer is formed under the action of centrifugal force to obtain a crucible green body;

[0129] (2) The green crucible was arc fired, and 8 g of barium carbonate powder was sprinkled into the green crucible during the firing process to obtain a crucible body, wherein the arc firing temperature was 2000° C. and the time was 30 min.

[0130] The quartz crucible prepared in this comparative example, Figure 2 As shown, the quartz crucible includes a protective layer 1 (0.01 mm thick), a transparent layer 2 (6 mm thick) and a bubble layer 3 (10 mm thick) which are arranged in sequence from the inside to the outside, wherein the protective layer 1 includes barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer 2 includes quartz sand and barium silicate, and the mass percentage of barium silicate is 0.29 ppm.

[0131] Test method:

[0132] (1) Bond strength test of protective coating: Ultrasonic testing is a commonly used technology that can be performed according to the standard "Nondestructive Testing - Ultrasonic Testing Method for Bond Strength of Coatings" (GB / T 38898-2020). This method is suitable for coating structures where the coating, substrate and bonding layer are all made of metal and non-metal materials with good sound permeability.

[0133] (2) Density test of protective coating: Detailed steps of the density test method of protective coating

[0134] The coating density test is usually carried out using the drainage method based on the Archimedes principle. The following are the detailed test steps based on the GB / T39688-2020 standard:

[0135] a. Sample preparation: Prepare protective coating samples of standard size and ensure that the sample surface is smooth and flat;

[0136] b. Measure the mass and volume of the uncoated substrate (crucible body) sample and calculate the density of the substrate (crucible body);

[0137] c. Measure the density of the coating sample: immerse the protective coating sample completely in water and measure its mass in water (immersion mass);

[0138] d. Calculate the volume of the protective coating sample by measuring the displacement volume of the sample in water or directly measuring it using a container of known volume;

[0139] e. Calculate the density of the protective coating sample: density = coating density / theoretical coating density*100%.

[0140] (3) Thermal expansion coefficient test of protective coating: The principle of measuring thermal expansion coefficient by laser interferometer is based on laser interferometry technology, which calculates the thermal expansion coefficient by measuring the length change of the sample when the temperature changes. The specific steps include:

[0141] a. Sample preparation: Fix the sample to be tested on the sample stage of the interferometer, ensuring that the length direction of the sample is aligned with the laser beam;

[0142] b. Adjust the optical path: adjust the laser, beam splitter and reflector to make the laser beam produce interference fringes on the sample surface;

[0143] c. Temperature control: Use the temperature control system to heat or cool the sample and record the temperature changes;

[0144] d. Data acquisition: As the temperature changes, the laser interference fringes will move. By measuring the amount of fringes moving, the length change of the sample can be calculated;

[0145] e. Data processing: Calculate the thermal expansion coefficient based on the original length and temperature change data of the sample.

[0146] (4) Service life test of quartz crucible: actual measurement of continuous crystal pulling in a furnace.

[0147] (5) Quartz crucible crystal pulling test: actual test of continuous crystal pulling in a furnace.

[0148] The above test results are detailed in Table 1 below:

[0149] Table 1 Quartz crucible and protective coating performance test results

[0150]

[0151]

[0152] According to the test data in Table 1, the preparation method of the quartz crucible in Examples 1 to 8 is to first form a uniformly distributed barium silicate coating on the inner surface of the quartz crucible, and then use a spraying process combined with carbon dioxide for gradient heat treatment to form a dense and uniform protective coating on the surface of the barium silicate coating. The protective coating can improve the bonding force between the protective coating and the inner surface of the quartz crucible, and at the same time improve the thermal stability and chemical stability of the coating, thereby improving the corrosion resistance and service life of the quartz crucible.

[0153] Compared with Example 1, during the preparation process, no barium hydroxide was added to the protective coating of Example 1, no nano-silicon dioxide was added to Example 2, and no boric acid was added to Example 3. The bonding strength and density of the protective coating decreased to varying degrees compared with Example 1, resulting in a decrease in the service life of the quartz crucible and the crystal pulling rate.

[0154] Compared with Example 1, Comparative Example 4 did not introduce carbon dioxide for heat treatment during the preparation process, and the bonding strength and density of the protective coating were significantly reduced compared with Example 1. The service life and crystal pulling rate of the quartz crucible were also significantly reduced compared with Example 1.

[0155] Compared with Example 1, the barium carbonate powder of Comparative Example 5 is applied by direct sprinkling during the melting process. Therefore, the barium carbonate is difficult to be evenly distributed during the melting process of the quartz crucible, resulting in a significant decrease in the bonding strength and density of the protective coating compared to Example 1, and a significant decrease in the service life of the quartz crucible and the crystal pulling rate.

[0156] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a quartz crucible, characterized in that: The steps include: preparing a crucible green body, wherein the crucible green body comprises a first quartz sand layer and a second quartz sand layer arranged in sequence from outside to inside, wherein the second quartz sand layer comprises quartz sand and barium carbonate, and the purity of the quartz sand in the first quartz sand layer is lower than the purity of the quartz sand in the second quartz sand layer; Firing the crucible green body to obtain a crucible body; The protective coating is sprayed onto the inner surface of the crucible body by using an inert gas, and then a gradient temperature increase heat treatment is performed after carbon dioxide gas is introduced to obtain a quartz crucible, wherein the protective coating includes 35wt% to 45wt% of barium hydroxide, 2.8wt% to 5wt% of nano-silicon dioxide and 4wt% to 10wt% of boric acid in mass percentage, and the quartz crucible includes a crucible body and a protective layer located on the inner surface of the crucible body, and the protective layer includes barium carbonate, nano-silicon dioxide and barium borate.

2. The method for preparing a quartz crucible according to claim 1, characterized in that: The preparation method includes at least one of the following features: (1) The amount of quartz sand added to the first quartz sand layer is 95 g to 100 g; (2) The amount of quartz sand added to the second quartz sand layer is 10 g to 15 g; (3) The mass ratio of the quartz sand to the barium carbonate in the second quartz sand layer is (10-15): (0.003-0.005); (4) The purity of the quartz sand in the first quartz sand layer is 6N to 13N; (5) The purity of the quartz sand in the second quartz sand layer is greater than 7N.

3. The method for preparing a quartz crucible according to claim 1, characterized in that: The crucible green body is arc fired to obtain a crucible body, wherein the arc firing temperature is 1700° C. to 2600° C. and the time is 30 min to 40 min.

4. The method for preparing a quartz crucible according to claim 1, characterized in that: The step of spraying the protective coating onto the inner surface of the crucible body using an inert gas comprises: Under vacuum conditions, the protective coating is sprayed onto the inner surface of the crucible body at a distance of 25 cm to 30 cm from the inner surface of the crucible body using a spray gun with a pressure of 20 psi to 40 psi.

5. The method for preparing a quartz crucible according to claim 4, characterized in that: The vacuum degree under the vacuum condition is 1200Pa to 15000Pa.

6. The method for preparing a quartz crucible according to claim 4, characterized in that: The spraying thickness of the protective coating is controlled to be in the range of 0.01 mm to 0.015 mm; and / or the spraying temperature of the protective coating is controlled to be in the range of 25° C. to 35° C.

7. The method for preparing a quartz crucible according to claim 1, characterized in that: The gradient temperature increase heat treatment comprises: after introducing carbon dioxide gas, heating to 40°C-45°C at 5°C / min-10°C / min for heat treatment for 5min-10min, and then heating to 75°C-80°C at 5°C / min-10°C / min for heat treatment for 15min-20min.

8. The method for preparing a quartz crucible according to claim 1, characterized in that: The carbon dioxide gas is introduced at a flow rate of 40 L / min to 100 L / min, and the introduction time is 25 min to 30 min.

9. A quartz crucible, characterized in that: The quartz crucible is prepared according to the method for preparing a quartz crucible according to any one of claims 1 to 8, and the quartz crucible comprises a protective layer, a transparent layer and a bubble layer arranged in sequence from the inside to the outside, wherein the protective layer comprises barium carbonate, nano-silicon dioxide and barium borate, and the transparent layer comprises quartz sand and barium silicate.

10. The quartz crucible according to claim 9, characterized in that: The quartz crucible includes at least one of the following features: (1) The thickness of the protective layer is 0.01 mm to 0.015 mm; (2) The mass percentage of barium silicate in the transparent layer is 0.05ppm to 0.1ppm; (3) The thickness of the transparent layer is 5 mm to 10 mm; (4) The thickness of the bubble layer is 12 mm to 15 mm.

Citation Information

Patent Citations

  • Preparation method of novel quartz crucible

    CN110629281A

  • Surface treated crucible for improving undislocation performance

    CN1149634A

  • Method for improving crystallization rate of re-put monocrystalline silicon and monocrystalline silicon preparation device

    CN115142121A

  • Preparation method of melted crystals

    KR1020110136758A

Cited By

  • Quartz crucible for monocrystalline silicon production and preparation method thereof

    CN120485938A

  • Quartz crucible for producing single crystal silicon and method for manufacturing the same

    CN120485938B

  • Crucible and manufacturing method thereof

    CN120758964A